Comprehensive Review of Herbal Extracts: Modern Pharmaceutical Uses, Phytochemical Composition, Extraction Methods, Historical Legacy - Surendra, Grandhi; Rao Kasula, Ramalingeswara; Ramakrishna Reddy, Malapati; Sharma, Sakshi; Kumari, Shalini; Khan, Sameer; Awasthi, Akansha; N Anjana Male, Ch K V L S (Journal of Neonatal Surgery, 2025)
Herbal extracts, rich in bioactive compounds such as alkaloids, flavonoids, and terpenes, have been integral to traditional medicine for millennia. This review explores the historical evolution of herbal extracts, tracing their origins from ancient China, India, and Egypt to their contemporary applications. It details various extraction methods, including maceration, distillation, and solvent extraction, emphasizing the efficiency of each technique in isolating specific compounds. The phytochemical diversity of herbal extracts is examined, highlighting the therapeutic potential of alkaloids, flavonoids, terpenoids, glycosides, saponins, and phenolic compounds. The review further delves into the applications of herbal extracts in modern pharmaceuticals, encompassing their roles as anti-inflammatory, antioxidant, cardioprotective, antimicrobial, anticancer, antidiabetic, immunomodulatory, and adaptogenic agents. Formulations and dosage forms of herbal extracts, such as tinctures, capsules, and topical applications, are also discussed. Regulatory considerations across different regions are outlined to underscore the importance of safety, efficacy, and quality control. Finally, the review addresses challenges such as standardization, regulatory hurdles, and the need for scientific validation, while also considering future prospects in personalized medicine, biotechnological advances, and evidence-based formulations.